AUTONOMY AND BIOMEDICAL RESEARCH IN LOW-INCOME COUNTRIES EXPERIENCES AND REFLECTIONS - BEHETS, Frieda (MEDECINE LEGALE DROIT MEDICAL, 2025)
Respect for autonomy is presented from a research ethics perspective that aims to generate new knowledge beneficial to society as part of an overarching pursuit of social justice. Respecting the autonomy of a research subject requires his or her informed consent except in specific cases. Numerous challenges thwart informed consent but tools can be developed that will facilitate the consent process. Qualitative or mixt methods formative research can identify possible challenges as well as potential solutions. Some concrete examples are presented that illustrate the advantages of conducting formative research before starting biomedical research. In resource-deprived contexts the autonomy of research and health professionals can be promoted as well as the autonomy of the broader local communities through implementation research that can strengthen capacity of various agents and structures.